Facile synthesis of pH-responsive sodium alginate/carboxymethyl chitosan hydrogel beads promoted by hydrogen bond. (15th February 2022) - Jing, Huijuan; Huang, Xin; Du, Xiaojing; Mo, Ling; Ma, Chaoyang; Wang, Hongxin
Abstract: In this work, a novel synthesis strategy of sodium alginate/carboxymethyl chitosan hydrogel beads promoted by hydrogen bond was described. The beads were prepared by dropping the blends of two polymers into the citric acid solution. Besides hydrogen bonding, electrostatic interactions were also involved in the formation of the hydrogel beads. The thermal stability experiments revealed that the more the content of carboxymethyl chitosan, the better the thermal stability of the beads. The beads exhibited excellent pH sensitivity, pH reversibility, and lactoferrin loading capacity. The swelling ratio of the bead and its protein releasing profile was pH-dependent, which could prevent premature protein release in the gastric environment. Also, the circular dichroism results demonstrated that lactoferrin could maintain its structure during the loading and releasing process. The obtained results revealed that the hydrogel beads prepared in this work could be used as a potential protein carrier for oral delivery. Graphical abstract: Unlabelled Image Highlights: A novel and green method was proposed to synthesize SA/CMCS hydrogel beads. Hydrogen bonding promoted the formation of the hydrogel beads. The beads showed excellent pH sensitivity and protein encapsulation capacity. The beads could prevent premature protein release in a harsh gastric environment.